Characterization of MWCNT-PEDOT: PSS Nanocomposite Flexible Thin Film for Piezoresistive Strain Sensing Application - Roopa Hegde; Koona Ramji; Swapna Peravali; Yallappa Shiralgi; Gurumurthy Hegde; Lavakumar Bathini (Advances in Polymer Technology)
Multiwalled carbon nanotubes (MWCNTs) were synthesized by the reduction of ethyl alcohol with sodium borohydride (NaBH4) under a strong basic solvent with the high concentration of sodium hydroxide (NaOH). Nanocomposites of different concentration of MWCNT dispersed in poly(3,4-ethylene dioxythiophene) polymerized with poly(4-styrene sulfonate) (PEDOT:PSS) were prepared and deposited on a flexible polyethylene terephthalate (PET) polymer substrates by the spin coating method. The thin films were characterized for their nanostructure and subsequently evaluated for their piezoresistive response. The films were subjected to an incremental strain from 0 to 6% at speed of 0.2 mm/min. The nanocomposite thin film with 0.1 wt% of MWCNT exhibits the highest gauge factor of 22.8 at 6% strain as well as the highest conductivity of 13.5 S/m. Hence, the fabricated thin film was found to be suitable for piezoresistive flexible strain sensing applications.